Interaction between DC-SIGN and DC-SIGNR with HHV-8 (LANA-1) and HIV-p24 in Castleman disease - Chetty, Dharshnee Rama (Division of Anatomical Pathology, 2019)
Background: Castleman disease (CD) is a lymphoproliferative disorder with four subtypes, some of which are aetiologically linked to Human Herpes virus 8 (HHV-8) which is known to cause diseases preferentially occurring in HIV-infected individuals. There has been a notable increase in the number of patients with HIV/HHV-8 associated CD diagnosed in the Groote Schuur hospital complex. Aims: The aim of the study was to determine the role of DC-SIGN, DC-SIGNR, p24 and HHV-8 (LANA-1) in Castleman disease. Our objectives were to identify the presence of DC-SIGN and DC-SIGNR in HHV-8 infected cells, determine whether HHV-8 and p24 (HIV) co-infection occurs in the same cells and to determine whether HHV-8 infects B and/or T cells. This study not only represents the largest and first immunophenotypic investigative evaluation of CD but also signifies the first double staining immunohistochemical analysis of CD diagnosed at Groote Schuur hospital. Methods: This was both a retrospective descriptive as well as an analytic cross-sectional immunohistochemistry study. Fifty cases of CD diagnosed at the Division of Anatomical Pathology, National Health Laboratory Service, Groote Schuur hospital over a ten and half year period were included in the study. Double immunohistochemistry was used to characterise HHV-8 infected cells using LANA-1 antibody, in conjunction with DC-SIGN, DC-SIGNR, p24, CD20 and CD3. Immunophenotypic analysis was then performed to assess 1) the number of infected HHV-8 cells and 2) number and distribution of cells co-expressing HHV-8 and DC-SIGN, DC-SIGNR, p24, CD20 and CD3. The immunophenotypic profiles were then compared to the CD morphologic subtypes. Results: The study cohort included 26 male and 24 female patients (M: F = 1.08:1), mean age 37.7 years. There were 16 hyaline vascular CD (HV-CD), 16 plasmablastic CD (Pb-CD). Nine plasma cell CD and 9 mixed-CD subtypes. There was a statistically significant association between HIV (n=45) and HHV-8 (n=40) positivity (p < 0.0002). CD4 counts and HAART enrolment were not predictive of CD development (p = 0.6120). Concurrent Kaposi sarcoma was seen in 16% (n=8) of the cohort. When comparing Pb-CD and HV-CD, there were statistically significant differences in density of LANA-1 infected cells (p<0.0002), LANA-1/DC-SIGN co-expressing cells (p <0.0072) and LANA-1/p24 co-expressing cells (p<0.0001). Conclusions: The findings of this study suggest that DC-SIGN may have a role in HHV-8 entry into cells. Furthermore, there is evidence that HIV and HHV-8 co-infection may function synergistically in CD. It is possible that DC-SIGN and DC-SIGNR facilitate dual viral entry into cells and influence viral replication and persistent infection.